Probing the role of the Epa1p tandem repeat region in Candida glabrata adhesion - Raposo, Colin J. (Tufts University. Tisch Library., 2018)
The aim in this project was the identification of function associated with variation in the repetitive cell surface adhesin Epa1p. Epa1p is responsible for the binding of the fungal pathogen Candida glabrata to host epithelial cells, a process necessary for infection. Submitted in partial fulfillment of the grant requirement of the Tufts Summer Scholars Program.